2019
DOI: 10.1093/ajh/hpz182
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of Blood Pressure in Patients With Hypertension-Related Multi-morbidity: Systematic Review and Individual Patient Data Meta-analysis

Abstract: BACKGROUND Studies have shown that self-monitoring of blood pressure (BP) is effective when combined with co-interventions, but its efficacy varies in the presence of some co-morbidities. This study examined whether self-monitoring can reduce clinic BP in patients with hypertension-related co-morbidity. METHODS A systematic review was conducted of articles published in Medline, Embase, and the Cochrane Library up to January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 48 publications
2
68
0
4
Order By: Relevance
“…37 In previous studies, HBPM had a marginal effect on BP when used in the absence of other interventions such as patient education, counseling by nurses or pharmacists, and telecounseling. 33,38,39 Finally, interventional studies showed that HBPM was not associated with improved BP control in patients with frequent medical visits. 40 Home blood pressure monitoring is already considered a better predictor of cardiovascular risk than clinical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…37 In previous studies, HBPM had a marginal effect on BP when used in the absence of other interventions such as patient education, counseling by nurses or pharmacists, and telecounseling. 33,38,39 Finally, interventional studies showed that HBPM was not associated with improved BP control in patients with frequent medical visits. 40 Home blood pressure monitoring is already considered a better predictor of cardiovascular risk than clinical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not provide any significant evidence to support the superiority of telemedicine for BP management in these patients. A recently published metaanalysis [50] investigated whether the effectiveness of self-monitoring of BP combined with a cointervention, including telemonitoring, varied by co-morbidity. Self-monitoring of BP combined with intense co-interventions was more effective than low-intensity self-monitoring in patients with obesity and possibly stroke, but not in patients with coronary artery disease, diabetes, or CKD.…”
Section: Patients With Cardiovascular or Renal Diseasementioning
confidence: 99%
“…While some patients omit writing down the heart rate, it is essential in determining whether a significant postural decrease in BP is associated with a compensatory increase in heart rate or not, which can be an early clue to autonomic causes of orthostatic hypotension. 5 , 6 Temperature checks and pulse oximeter readings are especially useful in identifying patients in whom COVID-19 might be suspected. The patient can be guided through these measurements by a medical assistant or nurse prior to the virtual visit.…”
Section: Ten Steps For a Patient-assisted Virtual Physical Examinatiomentioning
confidence: 99%